中枢神経疾患の機能障害を改善するための工夫 - 後藤, 淳 (関西理学療法, 2022)
Central nervous system disease is a disease that occurs in the central nervous system from the brain to the spinal cord due to various reasons. The pathology is diverse, and the symptoms are different even for the same disease. In order to develop physical therapy, it is important to evaluate the posture and movements of actual subjects. Physical therapy technique is considered to be whether the therapist can respond well to changes in the subject in a clinical setting. Here, we describe our own approaches for physical therapy for central nervous system diseases from the viewpoint of imitation, guidance, and voluntary movements.